Complement activation within the coeliac small intestine is localised to Brunner's glands. Issue 11 (November 1989) - Gallagher, R B; Kelly, C P; Neville, S; Sheils, O; Weir, D G; Feighery, C F
Abstract : Complement activation may play an important role in the pathogenesis of coeliac disease. In the present study immunohistochemical localisation of C3 and of a neoantigen exposed only on the terminal C5b-9 complement complex has been performed on small intestinal biopsy sections from newly diagnosed untreated coeliac patients, from coeliac patients on long-term gluten-free diet and from disease controls. Levels of C3 were markedly increased in treated coeliac patients compared with controls. Staining of C3 was concentrated subepithelially and within the centre of the lamina propria. No staining was detected at these sites using antibody to the neoantigen, however, strongly suggesting that the increased levels of C3 seen in the coeliac patients was the result of increased extravasation of serum proteins rather than complement activation. Surprisingly, complement activation was detected within the glands of Brunner. Positive staining using anti-C5b-9 neoantigen was found in all coeliac patients, both treated and untreated. Three of the 13 disease controls also showed reactivity with this antibody. This novel finding suggests that Brunner's glands, hitherto largely neglected structures, may play an important role in the development of coeliac disease.